Quota sampling design using self-administered questionnaire for brand loyalty study in the agriculture retail industry in Malaysia / Abaidullah Mustaffa … [et al.] - Mustaffa, Abaidullah; Hj. Hassan, Faridah; Musa, Rosidah; Abdul Rahman, Mariati (Institute of Research Management Innovation (IRMI), 2015)
Brand loyalty research involving quantitative approach using self administered questionnaires needs respondents which are sampled from consumers from the proposed industry. Quota sampling which is non-probability sampling can be used to sample respondents from the population. This paper elaborates the quota sampling design strategy to sample consumers from the agriculture retail industry in Malaysia. The questionnaire was developed based on survey instrument development to identify the dimensional structure of attitude and brand loyalty in the agriculture retail industry in Malaysia.